Efficient synthesis and excellent antimicrobial activity of star-shaped cationic polypeptides with improved biocompatibility. (22nd February 2021) - Liu, Hao; Zhang, Xu; Zhao, Ziyin; Yang, Fangping; Xue, Ruizhong; Yin, Lichen; Song, Ziyuan; Cheng, Jianjun; Luan, Shifang; Tang, Haoyu
Abstract : Star poly(L -lysine) homo- and copolymers with excellent antimicrobial activity and improved biocompatibility can be readily prepared by the combination of ultra-fast ring opening polymerization and efficient side-chain modification. Abstract : Antimicrobial peptides (AMPs) have been considered as a promising new tool to combat the antimicrobial resistance (AMR) crisis. However, the high toxicity and high cost of AMPs hampered their further development. Herein, a series of star poly(L -lysine) (PLL) homo- and copolymers with excellent antimicrobial activity and improved biocompatibility were prepared by the combination of ultra-fast ring opening polymerization (ROP) and side-chain modification. The amine-terminated polyamidoamine dendrimer (G x -PAMAM) mediated ROP of Nε- tert -butyloxycarbonyl-L -lysine N -carboxyanhydride (Boc-L -Lys-NCA) and γ-benzyl-L -glutamic acid-based N -carboxyanhydride (PBLG-NCA) was able to prepare star PLL homo- and copolymers with 400 residues within 50 min. While the star PLL homopolymers exhibited low minimum inhibitory concentration (MIC = 50–200 μg mL −1 ) against both Gram-positive and Gram-negative bacteria ( i.e., S. aureus and E. coli ), they showed high toxicity against various mammalian cell lines. The star PLL copolymers with low contents of hydrophobic and hydroxyl groups showed enhanced antimicrobial activity (MIC = 25–50 μg mL −1 ) and improved mammalian cell viability. Both SEM and CLSM results indicated the antimicrobial mechanism of membrane disruption.